Analyzing the Role of Stress and Rumination in Tension-Type Headaches and Migraine - Jamshidi, Fatemeh; Hosseini, Azam; Norouzi, Elham; Ebrahimkhani, Mehdi (Journal of Assessment and Research in Applied Counseling (JARAC), 2023)
Objective: The study aimed to investigate the role of stress and rumination in predicting the severity of tension-type headaches and migraines.Methods and Materials: This cross-sectional study involved 300 participants suffering from tension-type headaches and migraines in Tehran. Data were collected through questionnaires assessing headache severity, stress (using the DASS-21 scale), and rumination (using the Nolen-Hoeksema and Morrow Rumination Scale). Descriptive statistics, Pearson correlation, and multivariate regression analyses were conducted using SPSS-25.Findings: The study found that both stress and rumination positively and significantly correlate with headache severity. Multivariate regression analysis revealed that as stress and rumination scores increased, so did the severity of headaches, with standardized coefficients indicating a robust relationship.Conclusion: Stress and rumination play significant roles in exacerbating the severity of tension-type headaches and migraines. These findings underscore the importance of considering psychological factors in the management and treatment of these headache disorders, highlighting the need for integrative approaches that address both psychological and physiological aspects.